RELATIVE EFFICIENCY OF FIELD AND ONLINE STRATEGIES IN THE RECRUITMENT OF HIV-POSITIVE MEN WHO HAVE SEX WITH MEN - Vial, Andrea C. (AIDS Educ Prev, 2015)
Efforts to reach HIV-positive men who have sex with men (MSM) and link them to care must be expanded; however, finding and recruiting them remains a challenge. We compared the efficiency of three recruitment sources in reaching self-identified HIV-positive MSM with various characteristics. Relative to recruitment online and at clubs and bars, AIDS Service Organizations (ASOs) were significantly more efficient in reaching HIV-positive MSM in general. This was also true for those with specific characteristics of interest such as substance/stimulant use, and HIV-positive MSM who were racial/ethnic minorities. Both ASOs and online recruitment were more efficient than clubs and bars in reaching HIV-positive MSM not taking HIV medication. This was also the case for White HIV-positive MSM in general, and White HIV-positive MSM who used substances and stimulants. Online recruitment was also more efficient than clubs and bars in reaching HIV-positive MSM who were young across the board.